JEE maths #8

Algebra Level 5

Find the number of complex numbers z z satisfying the conditions z z ˉ + z ˉ z = 1 \left| \dfrac z{\bar z} + \dfrac {\bar z}z \right| = 1 and z = 1 |z| = 1 .

1 2 8 4 5

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Mar 30, 2017

From z = 1 |z|=1 , z = e θ i \implies z = e^{\theta i} . Then

z z ˉ + z ˉ z = 1 e θ i e θ i + e θ i e θ i = 1 e 2 θ i + e 2 θ i = 1 2 cos 2 θ = 1 cos 2 θ = ± 1 2 2 θ = ( n ± 1 3 ) π where n = 0 , 1 , 2... θ = 3 n ± 1 6 π = π 6 , π 3 , 2 π 3 , 5 π 6 , 7 π 6 , 4 π 3 , 5 π 3 , 11 π 6 \begin{aligned} \left| \frac z{\bar z} + \frac {\bar z}z \right| & = 1 \\ \left| \frac {e^{\theta i}}{e^{-\theta i}} + \frac {e^{-\theta i}}{e^{\theta i}} \right| & = 1 \\ \left| e^{2\theta i} + e^{-2\theta i} \right| & = 1 \\ \left| 2\cos 2\theta \right| & = 1 \\ \cos 2\theta & = \pm \frac 12 \\ 2\theta & = \left({\color{#3D99F6}n} \pm \frac 13\right) \pi \quad \quad \small \color{#3D99F6} \text{where }n=0,1,2... \\ \theta & = \frac {3n \pm 1}6 \pi \\ & = \frac \pi 6, \frac \pi 3, \frac {2\pi}3, \frac {5\pi}6, \frac {7\pi}6, \frac {4\pi}3, \frac {5\pi}3, \frac {11\pi}6 \end{aligned}

Therefore, there are 8 \boxed{8} solutions.

z z ˉ + z ˉ z = 1. a + i b a i b + a i b a + i b = ± 1 ( a + i b ) 2 + ( a i b ) 2 a 2 + b 2 = + 1..... ( 1 ) a n d ( a + i b ) 2 + ( a i b ) 2 a 2 + b 2 = 1........ ( 2 ) ( 1 ) 2 ( a 2 b 2 ) = a 2 + b 2 , a 2 3 b 2 = 0. a 2 = 3 b 2 ± a a n d ± b . . . 4 n u m b e r s . ( 2 ) 2 ( a 2 b 2 ) = a 2 b 2 , 3 a 2 b 2 = 0. 3 a 2 = b 2 ± a a n d ± b . . . 4 n u m b e r s . T o t a l 8 n u m b e r s . \left| \dfrac z{\bar z} + \dfrac {\bar z}z \right| = 1.\\ ~~~~\\ \implies~\dfrac{a+ib}{a-ib} +\dfrac{a-ib}{a+ib} =\pm 1 \\ ~~~~\\ \therefore~\dfrac{(a+ib)^2+(a-ib)^2}{a^2+b^2}=+ 1.....(1)\\ ~~~~\\ and~\dfrac{(a+ib)^2+(a-ib)^2}{a^2+b^2}=-1........(2)\\ ~~~~\\ (1)~~2(a^2-b^2)=a^2+b^2,~~\implies~a^2-3b^2=0.\\ ~~~~\\ \therefore~a^2=3b^2~~\implies~\pm~ a~ and~\pm~b...4~numbers.\\ ~~~~\\ (2)~~2(a^2-b^2)=-a^2-b^2,~~\implies~3a^2-b^2=0.\\ ~~~~\\ \therefore~3a^2=b^2~~\implies~\pm~ a~ and~\pm~b...4~numbers.\\ ~~~~\\ Total~~8~numbers.

Niranjan Khanderia - 3 years, 2 months ago
Rahil Sehgal
Mar 30, 2017

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...